2017
DOI: 10.1111/nyas.13380
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer chemotherapy–induced bone damage: pathobiology and protective effects of resveratrol and other nutraceuticals

Abstract: Intensive cancer chemotherapy causes significant bone loss, for which the mechanisms remain unclear and effective treatments are lacking. This is a significant issue particularly for childhood cancers, as the most common ones have a >75% cure rate following chemotherapy; there is an increasing population of survivors who live with chronic bone defects. Studies suggest that these defects are the result of reduced bone from increased marrow fat formation and increased bone resorption following chemotherapy. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…Since anthracycline-based combination chemotherapy remains to be the backbone for treating breast cancer nowadays, it is vital to develop preventive strategies for alleviating bone marrow and bone toxicities that may affect quality of life post chemotherapy. Recently, several nutraceuticals (including LCn3PUFA) have been found to have some efficacies to promote bone health under physiological conditions or during methotrexate chemotherapy [ 21 ]. Consumption of LCn3PUFA has been suggested to attenuate aging-related bone loss and preventing bone loss in ovariectomized models [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since anthracycline-based combination chemotherapy remains to be the backbone for treating breast cancer nowadays, it is vital to develop preventive strategies for alleviating bone marrow and bone toxicities that may affect quality of life post chemotherapy. Recently, several nutraceuticals (including LCn3PUFA) have been found to have some efficacies to promote bone health under physiological conditions or during methotrexate chemotherapy [ 21 ]. Consumption of LCn3PUFA has been suggested to attenuate aging-related bone loss and preventing bone loss in ovariectomized models [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, H&E-stained sections of MTXtreated group showed marked reduction in thickness of growth plate cartilage and marked reduction in chondrocytes number within the proliferative zone. These findings were explained by [16] who reported that MTX treatment was shown to decrease chondrogenesis, accompanied by increased apoptosis of chondrocytes in the growth plate cartilage. Also, significant reduction in the growth plate thickness following MTX treatment, as compared to the control, was reported by [17] .…”
Section: Discussionmentioning
confidence: 92%
“…However, the use of FA is controversial, as its overuse can reduce MTX treatment effects and cause cancer relapses. Thus, developing safe/effective solutions for MTX-induced bone defects is required for pediatric oncology [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Although intensifying use of chemotherapeutic agents such as methotrexate (MTX) and glucocorticoids including dexamethasone (DEX) has achieved great success in the management of pediatric malignancies, high prevalence of chemotherapy‐associated bone growth impairments has been found in cancer patients and/or survivors which could persist into adulthood and is with significant clinical burden (Crofton et al, 2000; Fan et al, 2011; Haddy et al, 2001; Su et al, 2017). For example, patients of acute lymphoblastic leukemia (ALL), the most common pediatric cancer, have an over 80% of survival rate following multiagent chemotherapy involving the combination treatment of MTX and DEX (Mitchell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%